(untitled) (GAIMS Journal of Medical Sciences, 2023)
Background: Perinatal asphyxia refers to an impairment of the normal oxygenation during birth and the ensuing adverse effects on the neonate. Low Apgar score is commonly used to as an indicator of asphyxia, but it may not be available in all newborns, especially in extramural babies. Also, Apgar score alone does not predict neurologic outcome as it is influenced by various factors. So, the present study was conducted to find correlation between Apgar score and urinary uric acid to creatinine ratio in babies with perinatal asphyxia. Methodology: The present study was an observational case control study conducted in tertiary care hospital in southern part of Gujarat state. We recruited 56 babies with moderate to severe asphyxia and compared them with 56 babies without asphyxia. Uric acid (UA) to creatinine (Cr) ratio was calculated on spot urine samples within 24 hours of birth and a Receiver Operator Curve (ROC) was plotted. Results: Mean UA/Cr ratio among cases was 2.58±1.15 as compared to control group where the ratio was 0.71±0.21 (p < 0.00001). Using the ROC curves, cut off of UA/Cr of 1.24 was found to have a sensitivity of 94.6% and specificity of 98.2%. Area under the curve was 98.8%. A significant negative linear correlation was found between urinary UA/Cr ratio and the Apgar score (r = -0.7188, p < 0.001) among cases. Conclusions: Urinary uric acid to creatinine ratio is a useful marker to diagnose perinatal asphyxia when Apgar scores are unavailable and also to judge the severity of asphyxia.